Pengembangan Bahan Ajar Media Audio Visual Berbasis Powerpoint untuk Menumbuhkan Minat Menulis Permulaan di Kelas I SD Negeri 5 Jatimulyo - Nur Aida Giona; Andri Wicaksono; M. Yanuardi Zain (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
This research is motivated by the unavailability of powerpoint-based audio-visual media in Indonesian subject. Learning media teaching materials are used only by using media teaching materials in the form of blackboards, so that in teaching and learning activities in class it is still not enough to make students enthusiastic in writing. Teaching materialls Audio Visual media is important because it maked it easier for educators to carry out learningm for students to study independently and in groups and carry out a given task. This Powerpoint-based audio visual media will help students learn to be fun, as well as very effective and accurate to increase student interest in learning. Based on the research results obtained material validation is 82% with the criteria “Very Eligible”. The media validation results are 90% with the criteria of “Very Eligible”. The small group trial resulted in an average value of 95% with the criteria of “Very Good”. Field trials obtained an average value of 95% with the criteria of “Verry Good”. The results of students responses to the media obtained an average result of 97% with the criteria of “Very Good”. Powerpoint-based audio visual media products to foster interest in iniial writing can be used as teaching materials for additional learning media by educators in a more effective and veried learning prosess, and can be distributed to grade 1 students.